Glycol thermal synthesis of the 45B5 bioactive borate glass: Structural, physical, and apatite mineralization in vitro - dos Santos, Verônica Ribeiro; Campos, Tiago Moreira Bastos; Thim, Gilmar Patrocínio; Borges, Alexandre Luiz Souto [UNESP]; de Sousa Trichês, Eliandra (Elsevier, 2023)
This work was performed aiming to develop a new and straightforward route for bioactive glasses obtention with minimal equipment and explore the structural, physical, and bioactivity properties of the resulting glass and its glass ceramics. Herein, the synthesis of the borate bioactive glass in the 45B5 composition (46.1 B2O3 – 26.9 CaO – 24.4 NaO – 2.6 P2O5, mol%) by the glycol thermal method was proposed; an original chemical route for bioactive glass obtention based on transesterification reaction between the precursors with a glycol. The suggested mechanism for the borate network formation was proven accurate, revealing a vitreous structure formed by ring-type metaborate structural units with a lamellar morphology upon calcination. Glass-ceramics obtained at 500 (45B5-500) and 700 °C (45B5-700) indicate the oxides were effectively incorporated into the network by crystallization of Ca–Na–B, Ca–B, and Na–B phases. The in vitro apatite mineralization assay performed on the glass and glass-ceramics revealed their great solubility and conversion rate into hydroxyapatite (HA, Ca5(PO4)3(OH)), which is taken as an indication of bioactivity. Besides HA, however, calcium carbonate species were identified at the early stages of mineralization for 45B5 and 45B5-500, suggesting the 45B5-700 glass-ceramic has a higher ability to form apatite as the majority of Ca2+ are directed to precipitate into hydroxyapatite. Overall, the 45B5 glass and glass-ceramics demonstrated their great bioactivity, having high application potential in soft tissue engineering on wound healing materials and devices, as incorporation in hydrogels and nanofibers. Furthermore, the glycol thermal method generated new perspectives for the synthesis of a broad range of bioactive glasses compositions and their application in tissue engineering.
Keywords: Biomedical applications; Glass; Glass-ceramics; Powders: chemical preparation